Stakeholders' perspectives on online interventions to improve mental health in eating disorder patients and carers in Germany. (7th July 2021) - Schmidt-Hantke, Juliane; Vollert, Bianka; Hagner, Franziska; Beintner, Ina; Hütter, Kristian; Nitsch, Martina; Jacobi, Corinna; Waldherr, Karin
Abstract: Background: Eating disorders are causing severe consequences for those affected as well as a high burden for their carers. Although there is a substantial need for psychological assistance, different factors are hindering access to support. Internet-based interventions can help to overcome these barriers. To date, there is only little knowledge on attitudes of potential users, facilitators (e.g. psychologists) and decision makers (e.g. health insurances) regarding these interventions. Methods: We conducted focus groups with potential users ( N = 30) and semi-structured interviews with potential decision makers ( N = 4). Potential facilitators ( N = 41) participated in an online survey. Stakeholders' experiences, attitudes, and their needs regarding Internet-based interventions for eating disorder patients and carers were assessed. Furthermore, hindering and fostering factors related to reach, adoption, implementation and maintenance were analyzed. Results: About two-thirds of the participating facilitators have heard or read about Internet-based interventions in general. In contrast, the other stakeholders mentioned to have no or little experience with such interventions. Factors like anonymity, availability and cost-effectiveness were seen as major advantages. Also disadvantages, e.g. lack of personal contact, limitations by disease severity and concerns on data safety, were mentioned. Stakeholders stated the need for interventions which are usable, evidence-based, tailored and provide personal support. Conclusion: Stakeholders considered Internet-based programmes to have more advantages than disadvantages. Effort should be put in providing systematic education to address prejudices. When offering an online intervention, stakeholders' needs, as well as a continuous evaluation and adaptation, have to be taken into account.